Allied health research positions: a qualitative evaluation of their impact. Issue 1 (December 2017) - Wenke, Rachel; Ward, Elizabeth; Hickman, Ingrid; Hulcombe, Julie; Phillips, Rachel; Mickan, Sharon
Abstract Background Research positions embedded within healthcare settings have been identified as an enabler to allied health professional (AHP) research capacity; however, there is currently limited research formally evaluating their impact. In 2008, a Health Practitioner industrial agreement funded a research capacity building initiative within Queensland Health, Australia, which included 15 new allied health research positions. The present project used a qualitative and realist approach to explore the impact of these research positions, as well as the mechanisms which facilitated or hindered their success within their respective organisations. Methods Forty-four AHP employees from six governmental health services in Queensland, Australia, participated in the study. Individual interviews were undertaken, with individuals in research positions (n = 8) and their reporting line managers (n = 8). Four stakeholder focus groups were also conducted with clinicians, team leaders and professional heads who had engaged with the research positions. Results Nine key outcomes of the research positions were identified across individual, team/service and organisational/community levels. These outcomes included clinician skill development, increased research activity, clinical and service changes, increased research outputs and collaborations, enhanced research and workplace culture, improved profile of allied health, development of research infrastructure, and professional development of individuals in the research positions. Different mechanisms that influenced these outcomes were identified. These mechanisms were grouped by those related to the (1) research position itself, (2) organisational factors and (3) implementation factors. Conclusions The present findings highlight the potential value of the research positions for individuals, teams and clinical services across different governmental healthcare services, and demonstrate the impact of the roles on building the internal and external profile of allied health. Results build upon the emerging evidence base for allied health research positions and have important implications for a number of stakeholders (i.e. individuals in the research positions, AHPs and their managers, university partners and state-wide executives). Key recommendations are provided for all stakeholders to enhance the ongoing impact of these roles and the potential advocacy for additional positions and resources to support them.